Hepatogenic Potential and Liver Regeneration Effect of Human Liver-derived Mesenchymal-Like Stem Cells - Jooyoung Lee; Jiwan Choi; Seoon Kang; Jiye Kim; Ryunjin Lee; Seongjun So; Young-In Yoon; Varvara A. Kirchner; Gi-Won Song; Shin Hwang; Sung-Gyu Lee; Eunju Kang; et al. (Cells, 2020)
Human liver-derived stem cells (hLD-SCs) have been proposed as a possible resource for stem cell therapy in patients with irreversible liver diseases. However, it is not known whether liver resident hLD-SCs can differentiate toward a hepatic fate better than mesenchymal stem cells (MSCs) obtained from other origins. In this study, we compared the differentiation ability and regeneration potency of hLD-SCs with those of human umbilical cord matrix-derived stem cells (hUC-MSCs) by inducing hepatic differentiation. Undifferentiated hLD-SCs expressed relatively high levels of endoderm-related markers (GATA4 and FOXA1). During directed hepatic differentiation supported by two small molecules (Fasudil and 5-azacytidine), hLD-SCs presented more advanced mitochondrial respiration compared to hUC-MSCs. Moreover, hLD-SCs featured higher numbers of hepatic progenitor cell markers on day 14 of differentiation (CPM and CD133) and matured into hepatocyte-like cells by day 7 through 21 with increased hepatocyte markers (ALB, HNF4A, and AFP). During in vivo cell transplantation, hLD-SCs migrated into the liver of ischemia-reperfusion injury-induced mice within 2 h and relieved liver injury. In the thioacetamide (TAA)-induced liver injury mouse model, transplanted hLD-SCs trafficked into the liver and spontaneously matured into hepatocyte-like cells within 14 days. These results collectively suggest that hLD-SCs hold greater hepatogenic potential, and hepatic differentiation-induced hLD-SCs may be a promising source of stem cells for liver regeneration.